A fuzzy decision system for genetically modified plant environmental risk assessment using Mamdani inference. Issue 3 (15th February 2015) - Camastra, Francesco; Ciaramella, Angelo; Giovannelli, Valeria; Lener, Matteo; Rastelli, Valentina; Staiano, Antonino; Staiano, Giovanni; Starace, Alfredo
Highlights A fuzzy system for environmental risk assessment of genetically modified plants is described. The fuzzy system is based on Mamdani inference. The Fuzzy System Risk Assessments have been validated on real world trial case studies. The system decisions have been considered coherent and consistent by human experts.